Student Perceptions Toward The Use of AI-Mediated In English Speaking Performance at Tenth Grade SMAN 19 Tebo - Cenb Rosella Agustin Ellbas; Merry Dewan Dita (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The incorporation of artificial intelligence (AI) in language education has provided new opportunities for students to practice English learning especially in speaking ability. This research explored what the students thought about speaking in English and whether or not they had positive opinions toward using AI-based learning to enhance their English speaking skill at the tenth grade of SMAN 19 Tebo. This research adopted a qualitative research design. Questionnaires and follow- up interviews with students who had used Replika AI as a tool for speaking practice were the methods of data collection. The findings indicated that students had different attitudes to speaking in English. Several students reported experiencing anxiety, lack of confidence, and fear of making mistakes when speaking in class. On the other hand, there were also some concerns regarding the tool’s artificial intelligence design of Replika AI. The interaction with an AI-service app for all participants interacting with the AI application was associated with English practice on their own terms and without feeling judged. Moreover, the program generated an interactive context where the students could practice their conversations, and build their ideas more confidently. As has been elaborated above, the results showed that Replika AI was seen as a helpful instrument to practice English speaking and reduced students’ anxiety of speaking. The study recommends that AI- mediated learning has the potential to be an alternative medium for speaking practice in the EFL context.